Determination of antibody responses to meningococcal antigens by ELISA. - Rosenqvist, E; Käyhty, H; Pollard, A (2001)
Enzyme-linked immunosorbent assay (ELISA, EIA) is a highly versatile and sensitive technique that can be used for quantitative as well as qualitative determination of almost any antigen or antibody. Reagents are stable, non-radioactive and, in most cases, commercially available. Owing to the simplicity and versatility of the method, ELISA represents probably one of the most used methods for studying antibody responses and antibody levels. Since Engvall and Perlman's first paper describing the ELISA in 1971 (1), almost all laboratories working in serology or immunology have designed their own assays with different protocols for coating with antigens, incubation conditions, detecting systems, and ways of reporting of the results. In most cases, there is no need for strict interlaboratory standardization of ELISAs and each laboratory will develop a system that suits their needs. However, for some ELISAs, e.g., used in diagnostic laboratories and in vaccine trials, standardization is important, and this is considered in "Meningococcal Disease" Edited by AJ Pollard and MCJ Maiden, (1a).